Gagates in Crimean middle jurassic sediments (Sudak): coal petrography, paleobotany, formation conditions - I. E. Stukalova; Т. А. Sadchikova; S. V. Naugolnykh; А. L. Chepalyga (Известия высших учебных заведений: Геология и разведка)
Background. The coal-bearing deposits of the Kopsel formation of the Bathonian-Callovian age of the Middle Jurassic near the city of Sudak (Crimea) are studied. The conducted lithological and mineralogical analysis of rocks, mainly sandstones and siltstones, with shell detritus, plant residues and coal lenses (gagates), made it possible to determine the coastal-marine and lagoon sedimentation conditions. The studied gagates are represented by structural vitrinite and belong to the humus group. Secondary minerals in coal seams and host rocks indicate the stage of early catagenesis. The botanical analysis revealed the coal-forming plants, belonging to a group of conifers of the araucaria family.Aim. To identify the facies-climatic and landscape conditions for the formation of gagates of the Kopsel formation, along with their composition, structure, and secondary changes. To demonstrate that the material composition of coals is the wood of gymnosperms, mainly conifers, rather than algal thalli.Materials and methods. The natural outcrops of the coal-bearing deposits of the Middle Jurassic of the Bathonian-Callovian stage of the Kopsel formation in the valley of the Kopsel River near the city of Sudak (Crimea) were studied. The lenses and interlayers of brown coal — gagate — present in these deposits were of particular interest. Gagate samples were studied both macroscopically (forms and occurrence conditions in the section) and microscopically (by coal petrography methods). To this end, double-sided polished sections were examined using a polarizing microscope and a Vega3 Tescan scanning microscope. The microanalysis of chemical elements was performed using an ULTM Max (GIN) microscope attachment. Paleobotanical studies of carbonified plant residues were carried out. The structure, texture and mineral composition of the rocks were studied in thin sections using a microscope. A mineralogical analysis was carried out using a D8 Advace X-ray diffractometer (gross composition in a powder diffractogram and composition of clays in a fraction of <0.001 mm) and a Vega3 Tescan (GIN) scanning microscope.Results. The comprehensive studies conducted in the new, unique location of coals in the Kopsel Formation of the Middle Jurassic (Bathonian-Callovian stage) in the valley of the Kopsel River determined the paleobotanical composition of coal-forming plants (with the predominance of conifers of the Araucariaceae type), the climatic and paleolandscape conditions for the formation of these coals on the northern outskirts of Tethys. The lithological and mineralogical features of rocks, mainly sandstones and siltstones, with shell detritus, plant residues and lenses of coals (gagates), make it possible to determine the facies conditions of sedimentation as coastal-marine and lagoonal, with fragments of avantdelta and proluvial, landslide deposits. The established secondary changes in the host rocks and the coals indicate the stage of early catagenesis, to which the stratum was subjected at the next stages of geological history.Conclusion. Peat accumulation and subsequent coal formation most likely occurred in shallow lagoons. The type of peat accumulation is paralytic, paragenetically related to the studied sediments. Post-sedimentation transformations of the rocks correspond to early catagenesis. These transformations were established by the presence of secondary calcite (by rock cracks and in the form of nodule formations), the abundance of authigenic gypsum, and the widespread replacement of pyrite framboids with iron oxide minerals. The interlayers of gagates have also undergone changes. In those places where organic matter is impregnated with carbonate solutions, the coal substance is exposed to heat, thus becoming optically opaque.